Immunoregulatory Effects of Mesenchymal Stem Cell-Derived Extracellular Vesicles on T Lymphocytes. Issue 12 (December 2015) - Del Fattore, Andrea; Luciano, Rosa; Pascucci, Luisa; Goffredo, Bianca Maria; Giorda, Ezio; Scapaticci, Margherita; Fierabracci, Alessandra; Muraca, Maurizio
The immunomodulatory activity of mesenchymal stem cells (MSCs) is largely mediated by paracrine factors. We have recently shown that the immunosuppressive effects of MSCs on B lymphocytes in peripheral blood mononuclear cell (PBMC) culture can be reproduced by extracellular vesicles (EVs) isolated from MSC culture supernatants. Here we investigated the effect of bone marrow-derived MSC-EVs on T cells on PBMC cultures stimulated with anti-CD3/CD28 beads. Stimulation increased the number of proliferating CD3 + cells as well as of regulatory T cells (Tregs). Coculture with MSCs inhibited the proliferation of CD3 + cells, with no significant changes in apoptosis. Addition of MSC-EVs to PBMCs did not affect proliferation of CD3 + cells, but induced the apoptosis of CD3 + cells and of the CD4 + subpopulation and increased the proliferation and the apoptosis of Tregs. Moreover, MSC-EV treatment increased the Treg/Teff ratio and the immunosuppressive cytokine IL-10 concentration in culture medium. The activity of indoleamine 2, 3-dioxygenase (IDO), an established mediator of MSC immunosuppressive effects, was increased in supernatants of PBMCs cocultured with MSCs, but was not affected by the presence of MSC-EVs. MSC-EVs demonstrate immunomodulatory effects on T cells in vitro. However, these effects and the underlying mechanisms appear to be different from those exhibited by their cells of origin.